Advances in dyslipidemia management for prevention of atherosclerosis: PCSK9 monoclonal antibody therapy and beyond - Wong, Nathan D.; Rosenblit, Paul D.; Greenfield, Rosenblit (Cardiovascular Diagnosis and Therapy; Vol 7, Supplement 1 (April 26, 2017): Cardiovascular Diagnosis and Therapy (Advances in Cardiovascular Disease Prevention), 2017)
In 2003, select families with familial hypercholesterolemia were first identified to have gain-of-function mutations for proprotein convertase subtilisin kexin type 9 (PCSK9) followed, in 2006, by the identification of those with lifelong low levels of LDL-C and lowered atherosclerotic cardiovascular disease (ASCVD) risk who had loss-of-function PCSK9 mutations. These discoveries led to the rapid development of PSCK9-targeted monoclonal antibody (PCSK9 mAb) therapies and, in 2015, 2 ‘fully-humanized’ PCSK9 mAbs (alirocumab and evolocumab) were marketed in the United States, Europe, and other countries. In a wide range of high risk patients, with and without ASCVD, these PCSK9 mAbs, as once or twice monthly subcutaneous injections, potently reduce LDL-C 50–65% beyond levels achieved by maximally tolerated statin therapy; approximately one-third of patients achieve LDL-C levels